1979
DOI: 10.1136/jnnp.42.10.924
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural basis for different pertechnetate uptake patterns by various human brain tumours.

Abstract: SUMMARY Patterns of pertechnetate uptake were correlated with ultrastructural properties of the endothelial wall in 14 human brain tumours. In tumours with reduced uptake of the radionuclide, intercellular tight junctions were observed whereas absence of intercellular tight junctions was characteristic of all tumours with an increased uptake of pertechnetate. In some tumours with increased uptake, fenestrated endothelial wall was seen while in others nonfenestrated wall was evident. We concluded that intercell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…In the current study only 2% of vessels in tumour, and none of the vessels examined in normal white matter or peritumour, had fenestrations . This observation is consistent with qualitative observations of others in the same tumour type (Bar-Sella et al 1979, Shibata, 1989 . Although fenestrations have been described in other tumour types that have metastasized to brain (Bar-Stella et al .…”
Section: Measurement Of Barrier-associated Vascular Structuresupporting
confidence: 94%
See 1 more Smart Citation
“…In the current study only 2% of vessels in tumour, and none of the vessels examined in normal white matter or peritumour, had fenestrations . This observation is consistent with qualitative observations of others in the same tumour type (Bar-Sella et al 1979, Shibata, 1989 . Although fenestrations have been described in other tumour types that have metastasized to brain (Bar-Stella et al .…”
Section: Measurement Of Barrier-associated Vascular Structuresupporting
confidence: 94%
“…Others (Long 1970, Hirano et al . 1974, Bar-Sella et al . 1979, Roy and Sarkar 1989 have reported an increase in vesicular density in tumour vessels in humans .…”
Section: Measurement Of Barrier-associated Vascular Structurementioning
confidence: 95%
“…Increased vascular supply, disruption of the blood-brain barrier, high-grade cancer, and viability of tumor cells are decisive factors related to increased Tc-99m MIBI uptake in brain tumors (9). Although we did not evaluate cytologic and ultrastructural features of tumor cells and capillaries in relation to these uptake mechanisms, a high-grade oligodendroglioma possesses cellular and endothelial features that favor increased Tc-99m MIBI uptake (10). Finally, Tc-99m MIBI is a substrate for P-glycoprotein, a transmembrane pump that acts as a gatekeeper by expelling drugs from (cancer) cells.…”
Section: Discussionmentioning
confidence: 96%
“…Ultrastructural studies of human glioma microvessels have revealed 'open' interendothelial cell tight junctions (12). Tight junctions not only separate distinct physiological compartments, but they also confer selectivity to the transepithelial flux of molecules and ions through the intercellular spaces between the epithelial cells, the so-called paracellular pathway (13).…”
Section: Discussionmentioning
confidence: 99%